Construction principles of semantic service-oriented architecture - D. Y. Kashalkin; V. A. Kurchidis (Моделирование и анализ информационных систем)
Construction principles of service - oriented architecture as a means of achieving adaptability and flexibility of distributed information system's infrastructure are suggested. Different variants of constructing of this architecture, it's main elements, their interoperability, methods of working with them are considered. The suggested architecture is based on the definition of the semantic service-oriented architecture style and provides semantic means of distributed components interaction thus providing new level of decision of information systems integration problem.